Exploring the effects of seasons, diurnal cycle, and heights on airborne pollen load in a Southeast Asian atmospheric condition - Juprasong, Yotin; Sirirakphaisarn, Sirin; Siriwattanakul, Umaporn; Songnuan, Wisuwat (Frontiers in Public Health, 2022)
Aeropollen can induce detrimental effects, particularly in respiratory airways. Monitoring local aeropollen is essential for the management of pollen allergic patients in each area. However, without resources for constant monitoring, pollen counts are subjected to biases imposed by the choices of sampling season, time of collection, and location. Therefore, the effects of these factors must be better understood. This study investigated the dynamics of aeropollen types through seasonal variation, diurnal cycle and different heights from the ground in Bangkok, Thailand. Aeropollen samples were collected for 12 months at the Faculty of Science, Mahidol University in Bangkok, using a RotoRod Sampler®. For the investigation of diurnal effect, pollen was collected at 7 a.m., 10 a.m., 1 p.m., 4 p.m., and 7 p.m. For the study of height effect, data were collected at 2, 10, and 18 meters above ground. This is the first study of the effects of diurnal cycle and height variation on airborne pollen count in Southeast Asia. The results showed the highest concentration of aeropollen was observed in November, which was at the beginning of the northeast monsoon season in Bangkok, whereas the lowest concentration was recorded in July (rainy season). Interestingly, the lowest airborne pollen concentration recorded in July was greater than the high level of most standards. Grass pollen was found as the major aeropollen. The highest total pollen concentration was detected at 1 p.m. The maximum pollen quantity was detected at 10 meters from the ground. However, the total aeropollen concentration was extremely high (> 130 grains/m3) at all elevated heights compared to other studies that mostly found at lower height (approximately 1-2 m above ground). The result suggested that pollen concentrations of most pollen types increased as height increased. This study also illustrated the correlation between aeropollen quantity and local meteorological factors. This aeropollen survey reported that pollen concentration and diversity were affected by seasonal variation, diurnal cycle, and height from the ground. Understanding these relationships can help with predictions of aeropollen type and quantity.